Burden of Restricted Activity and Associated Symptoms and Problems in Late Life and at the End of Life. Issue 12 (2nd October 2018) - Gill, Thomas M.; Allore, Heather G.; Gahbauer, Evelyne A.; Murphy, Terrence E.
Abstract : Objectives: To compare rates of restricted activity and associated symptoms and problems in the last 6 months of life with those in the period before the last 6 months of life. Design: Prospective cohort study. Setting: Greater New Haven, Connecticut. Participants: Community‐living persons aged 70 and older (N=754). Measurements: The occurrence of restricted activity (staying in bed for at least half the day or cutting down on usual activities) and 24 prespecified symptoms and problems leading to restricted activity was ascertained monthly for nearly 19 years. Results: Rates of restricted activity per 100 person‐months were 36.5 in the last 6 months of life versus 16.1 in the period before the last 6 months of life ( P <.001). Of 737 participants with 1 month or more of restricted activity, rates of restricting symptoms per 100 person‐months of restricted activity ranged from 8.0 for frequent or painful urination to 65.6 for been fatigued, and rates of restricting problems ranged from 0.1 for problem with alcohol to 23.4 for been afraid of falling. Rates were significantly higher in the last 6 months of life than in the prior period for 13 of the 24 restricting symptoms and problems ( P <.05), most notably for shortness of breath (38.6 vs 21.8), weakness (37.3 vs 18.9), and confusion (31.2 vs 9.8). Mean (standard error) number of restricting symptoms and problems was significantly higher in the last 6 months of life (6.1 (0.1)) than in the prior period (4.7 (0.03)) ( P <.001). Conclusion: Rates of restricted activity and associated symptoms and problems are substantially greater in the last 6 months of life than in the period before the last 6 months of life. Enhanced palliative care strategies may be needed to diminish the burden of distressing symptoms and problems at the end of life.J Am Geriatr Soc 66:2282–2288, 2018 .